Ultrasound Biomicroscopy Might Predict the Outcome of Phacoemulsification-Visco Dissection in Medically Controlled Primary Angle-Closure Glaucoma Eye With Extensive Peripheral Anterior Synechia - Gong, Haijun; Dong, Xu; Zheng, Bingru; Gao, Xinbo; Chen, Liming; Zhang, Simin; Zuo, Chengguo; Lin, Mingkai (Frontiers in Medicine, 2021)
Objective: The treatment procedures of primary angle-closure glaucoma (PACG) with extensive peripheral anterior synechia (PAS) is a subject of debate. This study is to investigate the clinical features of phacoemulsification (Phaco)-visco dissection in medically controlled PACG patients with PAS > 180° and evaluate the predictability of Ultrasound Biomicroscopy (UBM) parameters on postoperative intraocular pressure (IOP). Methods: 48 eyes (48 patients) with acute angle-closure glaucoma (AACG) and 30 eyes (30 patients) with chronic angle-closure glaucoma (CACG) were prospectively included. All patients underwent phaco-viscogoniolysis and foldable lens implantation and were followed for one year after surgery. We analyzed preoperative and postoperative IOP, the numbers of anti-glaucoma medicine, the visual field value, the extent of PAS, and UBM parameters alterations, and evaluated the correlation between preoperative UBM parameters and one-year postoperative IOP. Results: IOP reduced significantly from 16.24 ± 4.33 mmHg to 14.49 ± 3.69 mmHg in AACG group and from 16.16 ± 3.69 mmHg to 14.31 ± 4.12 mmHg in CACG group, and PAS decreased significantly from 270 ± 60.33° to 171 ± 56.44° in AACG group and from 285 ± 70.46° to 168 ± 61.32° in CACG group, and the number of anti-glaucoma drugs decreased significantly in both groups. Several UBM parameters, including anterior chamber depth, trabecular iris angle, and peripheral iris thickness 500 increased while iris convex reduced considerably in the two groups, and angle opening distance 500 and trabecular-meshwork ciliary process angle increased significantly only in AACG group. One-year postoperative IOP correlated with preoperative angle opening distance 500 and trabecular iris angle negatively and iris convex positively. Conclusion: Phaco-visco dissection can effectively reduce IOP, the numbers of glaucomatous medications, and PAS in medically controlled PACG patients with extensive PAS. UBM parameters might be valuable for analyzing postoperative anterior segment structure and predicting postoperative IOP of Phaco-visco dissection in PACG patients with extensive PAS.